Development of multiple w/o/w emulsions showing prolonged antiinflammatoryy activity of nimesulide - Tandon P.; Mishra B. (My University, 2025)
Three multiple w/o/w emulsions containing nimesulide were prepared using three different formulae and were evaluated in vitro in pH 7.4 phosphate buffer and in vivo in carregeenin induced rat paw oedema model to investigate the drug release characteristics and prolonged release potential of multiple w/o/w emulsions. The results were compared with marketed suspension of nimesulide. Multiple emulsions provided slow and controlled release of nimesulide with prolonged antiinflammatory activity in rats in comparison to drug suspension. The in vitro and in vivo data of formulations showed good correlation between in vitro and in vivo results.